(untitled) (Journal of Universal Science Research, 2025)
Human Resources (HR) has evolved significantly in the 21st century. No longer simply a function of managing employee benefits and payroll, HR now plays a crucial role in shaping organizational culture, talent acquisition, and employee engagement. This paper explores the evolving role of HR in the 21st century, examining how HR professionals are adapting to the challenges of a rapidly changing workforce, technological advancements, and a globalized business environment.